2011
DOI: 10.1037/a0025195
|View full text |Cite
|
Sign up to set email alerts
|

Resilience: Enhancing well-being through the positive cognitive triad.

Abstract: The present study tested whether the relationships among resilience, life satisfaction, and depression could be explained by positive views toward the self, the world, and the future (positive cognitive triad). Structural equation modeling and mediation analyses were conducted based on 1,419 college students in Hong Kong. The model of positive cognitive triad as mediator between resilience and well-being fit the data (comparative fit index = .94, Tucker-Lewis index = .93, root-mean-square error of approximatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
194
4
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(225 citation statements)
references
References 64 publications
18
194
4
9
Order By: Relevance
“…Meanwhile, Mak, Ng and Wong (2011) reported that individuals with psychological stability have positive cognitions related to oneself, the world, and the future; this situation contributes to the development of one's thoughts of a positive future, thus preventing depression. However, childhood negative experiences have a negative effect on individual's thoughts and belief systems; there is also a relationship between physical, emotional, and sexual abuse experiences and an individual's negative beliefs about himself/herself, other people and the world, and such a condition leads to mental symptoms (Kaysen, Samuel, Mastnak, and Resick, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Mak, Ng and Wong (2011) reported that individuals with psychological stability have positive cognitions related to oneself, the world, and the future; this situation contributes to the development of one's thoughts of a positive future, thus preventing depression. However, childhood negative experiences have a negative effect on individual's thoughts and belief systems; there is also a relationship between physical, emotional, and sexual abuse experiences and an individual's negative beliefs about himself/herself, other people and the world, and such a condition leads to mental symptoms (Kaysen, Samuel, Mastnak, and Resick, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have begun to integrate resilience constructs into cognitive developmental theories of risk for depression (Hjemdal, Aune, Reinfjell, Stiles, & Friborg, 2007;Hjemdal, Vogel, Solem, Hagen, & Stiles, 2011;Keyfitz et al, 2012;Mak, Ng, & Wong, 2011) to better understand and prevent psychopathology (Masten, 2001;2011). In studies of nearly 400 younger adolescents (aged 13 to 15; Hjemdal et al, 2007), and 300 older adolescents (aged 14 to 18; Hjemdal et al, 2011), higher levels of resilience were associated with lower levels of depressive symptoms.…”
Section: Cognitive Schemas and Resiliencementioning
confidence: 99%
“…In studies of nearly 400 younger adolescents (aged 13 to 15; Hjemdal et al, 2007), and 300 older adolescents (aged 14 to 18; Hjemdal et al, 2011), higher levels of resilience were associated with lower levels of depressive symptoms. Interestingly, in a sample of 1400 university students, positive cognitions mediated the relationship between resilience and depression such that students with higher levels of resilience had more positive cognitions and lower levels of depressive symptoms (Mak et al, 2011). …”
Section: Cognitive Schemas and Resiliencementioning
confidence: 99%
“…It facilitates recovery among the somatically ill (Steward & Yuen, 2011) and it is connected with improved health, both physical and mental (Block & Kremen, 1996;Hall et al, 2010;Mak et al, 2011;Perfect & Jaramillo, 2012;Sołtys, 2013).…”
Section: Resiliency As a Health Resourcementioning
confidence: 99%
“…It is a disposition towards being able to interpret oneself, one's social surroundings and future in a way that ensures individual adequate functioning in various areas of life including work, interpersonal relations as well as physical and mental health (Charney, 2004;Klohnen, 1996;Mak, Ng, & Wong, 2011;Wells, 2009). …”
Section: Resiliency As a Health Resourcementioning
confidence: 99%